Bilateral fuchs uveitis syndrome in a patient with cryopyrin-associated periodic syndrome: A case report - Balbaba, Mehmet; Canleblebici, Mehmet; Yıldırım, Hakan; Celiker, Ulku (Gazi Eye Foundation, 2024)
In this case report, we aim to report an unusual case of in a patient with cryopyrin-associated periodic syndrome (CAPS) who had bilateral Fuchs uveitis syndrome (FUS). She had history of arthritis and sensorineural hearing loss and her ophthalmic examination revealed that both eyes had diffuse stellate keratic precipitates, diffuse stromal iris atrophy, anterior chamber cells and vitreous inflammation. The right eye intraocular pressure was high and the left one was normal. In addition, she had bilateral optic disc pallor. After genetic consultation, NRLP3 gene mutation was detected and was diagnosed CAPS and treated with anakinra. Despite maximum topical anti-glaucomatous medication, right intraocular pressure could not be controlled and then the patient had Ahmed glaucoma valve implantation. Inflammation and intraocular pressure elevation were not observed in the patient’s follow-up. In patients with CAPS, FUS uveitis which is rarely seen bilaterally, may be a component of ocular findings or may be incidental finding that is unique to our case. Copyright © 2024 The author(s).
Keywords: Cryopyrin associated periodic syndromes; fuchs uveitis syndrome; glaucoma NLRP3 gene mutation